Analisis Transparansi KPU Dalam Meloloskan Partai Ummat â€œImplementasi PKPU No 6 Tahun 2018â€ - Wiji Utomo, Wahyu (Prodi Tata Negara (Siyasah) IAIN Langsa, 2023)
One of the characteristics of democracy that is growing is the implementation of honest and fair elections. The 2024 election will certainly invite the political desire of many people to participate directly in it. Setting up a new party is one of the fastest ways to gain power. The emergence of the Ummah Party is one of the cases that is quite interesting to study, where previously the party was reported as TMS by the KPU and then, not so long ago, it was allowed to pass verification by the KPU, which of course leaves millions of questions unanswered to this day. The main question in this study is how the KPU is able to carry out the mandate of the law, especially on the issue of data and information transparency, and how the KPU is able to implement PKPU No. 6 of 2018 regarding data verification, which is suspected by many to be very deceptive and also suspected of fraud. As a result, the researchers' role here is to examine the transparency of data and information in the KPU's passage of the Ummah Party. The problems addressed in this study were addressed using descriptive qualitative methods as well as data analysis with reference to the enundang invitation regulations. From the results of the study, it was found that there were two manipulative actions associated with the lack of transparency of the KPU in providing data and information to the wider community, especially to the participants of new political parties.